Solitary Duodenal Metastasis from Renal Cell Carcinoma with Metachronous Pancreatic Neuroendocrine Tumor: Review of Literature with a Case Discussion - Baghmar, Saphalta; Shasthry, S M; Singla, Rajesh; Patidar, Yashwant; Bihari, Chhagan B; Sarin, S K (Indian Journal of Medical and Paediatric Oncology, 2019)
Renal cell cancinoma (RCC) is a unique malignancy with features of late recurrences, metastasis to any organ, and frequent association with second malignancy. It most commonly metastasizes to the lungs, bones, liver, renal fossa, and brain although metastases can occur anywhere. RCC metastatic to the duodenum is especially rare, with only few cases reported in the literature. Herein, we review literature of all the reported cases of solitary duodenal metastasis from RCC and cases of neuroendocrine tumor (NET) as synchronous/metachronous malignancy with RCC. Along with this, we have described a unique case of an 84-year-old man who had recurrence of RCC as solitary duodenal metastasis after 37 years of radical nephrectomy and metachronous pancreatic NET.
Keywords: Late recurrence; pancreatic neuroendocrine tumor; renal cell carcinoma; second malignancy; solitary duodenal metastasis